Analisis Kesesuaian dan Daya Dukung Kawasan Ekowisata Pantai Kategori Rekreasi di Pantai Sekunyit Kabupaten Kaur - Nara Agustin; Yar Johan; Mukti Dono Wilopo (Universitas Bengkulu, 2025)
Beach ecotourism is an ecotourism activity conducted in coastal areas in general by utilizing coastal resources and water levels. Sekunyit Beach is one of the beaches located in South Kaur District which is directly adjacent to the Indian Ocean. South Kaur district has an area of land area reaching 92.75 km2. This study aims to analyze the carrying capacity of recreational category coastal ecotourism area in Sekunyit Beach, Kaur Regency. The method performed in this study is the survey method. The results of the research on recreational category beach ecotourism in Sekunyit Beach obtained the results of the appropriate category (S2) and very appropriate (S1) with the Ecotourism Conformity Index (IKE) of 80,86% - 85,15%. While the value of the carrying capacity of sekunyit beach area ranges from 97 - 124 (people / day). Keywords: Area support capacity, Coastal ecotourism, Regional suitability, Scenic Beauty Estimation, Sekunyit Beach